Marxist Ideology, Identity Crisis and Existentialism in Richard Wright’s “The Outsider” - Tiwari, Diwakar (Journal of Advanced Research in English & Education; Vol 8 No 1 (2023): Journal of Advanced Research in English & Education, 2023)
The present paper deals with the American blacks’ attempt to seek all the means possible to establish their own identity. During the thirties, the Marxist ideology attracted thousands of Blacks who believed to have found in it the solution of their problem. But the vast majority of them quickly realized that the communist party wanted simply to use them. Richard Wright’s great disillusionment manifested itself in a novel in which he denounced an ideology thirsting after power and prepared to do anything to achieve its ends. The Outsider (1953) is a powerful existential novel and Cross Damon is its memorable existential hero fighting the battles of life. It is a novel that treats seriously problems of freedom, ethicsand morality, the dilemma of politics and religionand the paradox of racism in a democracy. The novel is concerned with the meaning of being - the significance of life in a universe that makes no particular judgments about the value of man. How to cite this article: Tiwari D. Marxist Ideology, Identity Crisis and Existentialism in Richard Wright’s “The Outsider”. J Adv Res Eng & Edu 2023; 8(1): 1-2. DOI: https://doi.org/10.24321/2456.4370.202301